ANALISIS SENSITIVITAS PADA PEMODELAN AIRTANAH MENGGUNAKAN METODE FINITE DIFFERENCE PADA KONDISI STEADY STATE DI KAB BANTUL PROV. YOGYAKARTA - satria fitrio; Tedy Agung C; Barlian Dwinagara; Muhammad Iqbal Ansori (KURVATEK, 2021)
Groundwater modeling is a form or digital image both 2D and 3D that can represent or approach the real form in the field. Groundwater modeling is made to show an overview or system of water flow under the ground surface. Groundwater is an important component in the hydrogeological cycle and groundwater management is very necessary so that the sustainability or the groundwater order system can be well maintained in the future. The purpose of this study is to determine the modeling of groundwater and groundwater distribution patterns from the calibration process in steady state conditions using the MODFLOW program. Groundwater modeling calibration used aims to validate the suitability of the model results with field conditions. The calibration is carried out using shallow wells of at least 67 community wells by combining topographic parameters, hydraulic conductivity, recharge, storativity, constant head, and ground water level that have been processed in the Modflow computational program. The results of the sensitivity analysis of modeling calibration are carried out into several stages of calibration scenarios so that the results that are closest to the standard criteria for groundwater models are obtained. Keyword: Groundwater modeling, Modflow, Calibration, groundwater, steady state